2002
DOI: 10.1177/002076402128783208
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Carers by Relatives with Severe Mental Illness

Abstract: Verbal and physical abuse are not infrequent problems facing family members caring for a relative with severe mental illness. Some of the risk factors for such abuse can be identified. Care plans for family carers could usefully target risk reduction strategies to minimise the occurrence of abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 10 publications
3
59
2
1
Order By: Relevance
“…(Mutter eines schizophrenen Pa− tienten). Auch Drohungen und andere verbale Übergriffe von Pa− tienten auf Angehörige (Beschimpfungen, Zornausbrüche des Er− krankten) [49,50] wie insbesondere körperliche Bedrohungen und Übergriffe [51] werden von Angehörigen als belastend ge− nannt. Nach Katschnig u. Mitarb.…”
Section: äNgste Und Sorgen Infolge Mangelnder Informationenunclassified
“…(Mutter eines schizophrenen Pa− tienten). Auch Drohungen und andere verbale Übergriffe von Pa− tienten auf Angehörige (Beschimpfungen, Zornausbrüche des Er− krankten) [49,50] wie insbesondere körperliche Bedrohungen und Übergriffe [51] werden von Angehörigen als belastend ge− nannt. Nach Katschnig u. Mitarb.…”
Section: äNgste Und Sorgen Infolge Mangelnder Informationenunclassified
“…Family carers for younger adults with mental illness have reported high levels of abuse from the people they care for. In a UK Community Mental Health Team (CMHT) survey, 22% of family carers reported that they had been threatened with violence, and 42% verbal abuse, by the care recipient (CR) in the last year 7. Higher rates of abuse were associated with poor relationships between patients and their families, and a patient history of poly-drug misuse and previous criminal offences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from animal models of Huntington's disease show significant benefits from treatment with E-EPA [Murck and Manku, 2007]. An open label study in humans reported a beneficial effect of E-EPA on motor function [Vaddadi et al, 2002] and this was confirmed by a small placebo-controlled trial in late-stage Huntington's disease [Puri et al, 2002]. A recent double-blind randomised, placebo-controlled study with E-EPA showed no benefit, but there were some promising data from a subgroup, suggesting that further studies are warranted [Puri et al, 2005].…”
Section: Huntington's Diseasementioning
confidence: 99%